(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Societies, as evolutionists argue, would transform from a simple to complex system. The governance pattern and the leadership must be in tandem with the transformation. In this age of dynamism - where legal-rational authority has already got momentum - it is the critical job for a head of the state even to maintain the status quo of administration. But still there is a rise in charismatic leaders. This article inquires the current state of relationship between ‘charismatic leadership’ and ‘governance’. By doing so, the article advances with comparative study of NGO governance or governing of the NGOs by popular leaders of world - Mr. Modi and Mr. Putin. This paper intends to interlink ‘personality trait’ and ‘governance’ of two leaders, in matters related to taming fraud NGOs. This paper adopts analytical method and in particular employs comparative method.